ANALISIS ESTIMASI REPRODUKSI DASAR MODEL MATEMATIKA PENYEBARAN PENYAKIT TUBERKULOSIS DI BIMA, INDONESIA - Ariyanto Ariyanto; Rapmaida M Pangaribuan; Zakarias S Ngara; Keristina Br Ginting (J-ICON : Jurnal Komputer dan Informatika, 2022)
The spread of covid-19 poses a threat to the transmission of diseases related to the lungs, including TB. TB is one of the main problems that is still easily found in various areas, including Bima Regency, NTB. To find out the dynamics of the distribution and the strategy to solve it, it is necessary to conduct research from various aspects, including the mathematical aspect. One of the important indicators in mathematical epidemiology is the basic reproduction ratio. Therefore, this study was conducted to determine the estimated value of the basic reproduction number, and the relationship between the rate of cure of the disease and the basic reproduction value using a mathematical model for the dynamics of the spread of TB tuberculosis in Bima Regency. The method used in this study is the early-take off-rate method, which is estimating the initial growth of the infected population. Bima Regency is included in the TB disease emergency category because from January 2020 to May 2022, 1,245 new cases of infected people were found, and the occurrence of the covid-19 pandemic in the last two years has contributed to a decrease in TB disease cases in Bima Regency. Based on the results of research data analysis, the spread of TB disease in Bima Regency is included in the endemic category with the indicator value of being in the range between 2 and 3. The spread of TB disease in Bima Regency will disappear from the population if the value of the disease transmission rate is below 0.168 with the healing rate is greater (or the treatment period is shorter).